Indonesian Tea Export Performance - Tupamahu, Yonette Maya; La Kamisi, Haryati (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
This study aims to analyze the trend of Indonesian tea exports for the 2000-2020 period and export forecasts for the 2021-2025 period, as well as analyze the factors that influence Indonesian tea exports. The data used is a time series from 2000 to 2020. To produce an efficient and consistent model, Stationarity Test is needed. Analysis of Indonesian tea exports using the method of Ordinary Least Square (OLS), classical assumption test, F-test and t-test. The results of the stationarity test and the classical assumption show that the data is stationary at the first difference level and the model is BLUE. The results of the study are as follows: first, the trend of Indonesian tea exports from 2000 to 2020 fluctuated with a downward trend. The results of forecasting Indonesia's tea exports for the period 2021 to 2025 show that export volumes tend to decline by an average of 12.3%. Second, Indonesian tea exports in year t are influenced by Indonesian tea production in year t and the exchange rate of the Rupiah against the US Dollar in year t, while world tea prices in year t have no significant effect.